Entry Modes for British MNCs into China - Phillips, Alexander (2013)
China has undergone massive economic reforms and institutional changes over the last 3 decades. Increasingly liberalized government regulations and the opening up of the Chinese market have attracted British MNCs to enter into this ‘dream market’. This paper seeks to primarily explore the factors that affect the entry mode selection of British MNCs. It will also seek to investigate how the current institutional environment affects entry mode selection. This paper uses a case study method to analyze two firm’s entries into China: Tesco and Jaguar Land Rover. A number of country specific, firm specific, location specific, venture specific and industry specific factors that influence entry mode selection have been identified. This paper shows that the institutional environment in China still has a big impact on entry mode selection.